2017
DOI: 10.1097/qad.0000000000001594
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcomes among HIV-infected veterans receiving atazanavir

Abstract: Objective: Patients with HIV infection have an increased risk of cardiovascular disease compared with uninfected individuals. Antiretroviral therapy with atazanavir (ATV) delays progression of atherosclerosis markers; whether this reduces cardiovascular disease event risk compared with other antiretroviral regimens is currently unknown. Design: Population-based, noninterventional, historical cohort study conducted from 1 July 2003 through 31 December 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Three studies did not provide sufficient information necessary to assess the study quality, as they were reported and available as conference abstract/poster 55 57 63. The eligibility criteria were clearly defined in the majority of studies (94%), description of study participants/ groups was sufficient (100%); however, the exposure or outcome was not adequately ascertained in 15 studies (47%)8 12 24 52 54 56 60 63–70; 1 (7%) of which was published as an abstract63 (see online supplementary appendix table 3: risk of bias in the included studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies did not provide sufficient information necessary to assess the study quality, as they were reported and available as conference abstract/poster 55 57 63. The eligibility criteria were clearly defined in the majority of studies (94%), description of study participants/ groups was sufficient (100%); however, the exposure or outcome was not adequately ascertained in 15 studies (47%)8 12 24 52 54 56 60 63–70; 1 (7%) of which was published as an abstract63 (see online supplementary appendix table 3: risk of bias in the included studies).…”
Section: Resultsmentioning
confidence: 99%
“…When the analysis was limited to two studies comparing recent PI exposure to no exposure,3 63 similar results were found (RR: 1.40; 95% CI 1.16 to 1.69 (data not shown)). For the individual PIs, there was no association between either atazanavir,52 64 66 68 saquinavir,52 68 or nelfinavir exposure,52 68 and MI risk, compared with no exposure (online supplementary appendix figure A4).…”
Section: Resultsmentioning
confidence: 99%
“…The average duration of HIV diagnosis until the beginning of the ATV regimen was 7.1 ± 6.8 years, with variations from a few weeks to 26 years. Choosing ATV therapies were justified as following: 26.6% guidelines recommendations for the first-line ARV, 46.6% failures of previous therapy, 18.3% adverse events of previous therapy, especially metabolic and cardiovascular events, 8.3% improving convenience for better adherence of experienced patients [9] .The pre-existing cardiovascular co-morbidities that counted for choose ATV as preferred PI were hypertension (18/60), cardiomyopathy (4/60), myocardial infarction (1/60), ischemic heart disease (2/60) and stroke (1/60) [10,11]. Combination antiretroviral therapies can be atherogenic and could increase stroke risk.…”
Section: Resultsmentioning
confidence: 99%
“…Therapies with ATV were initiated from 2009 until 2016, when updated recommendations of treatment guidelines for the first-line antiretroviral have been preferred other novel drugs [10].…”
Section: Resultsmentioning
confidence: 99%
“…100 Some analyses suggest that among the PIs, atazanavir may be preferred as a lower-risk option. 101,102 Careful assessment of cardiovascular risk factors in these patients, including initiation of primary prevention therapies as indicated, is warranted.…”
Section: Pharmacokinetic Interactionsmentioning
confidence: 99%